Modern traditional games improve early childhood social-emotional skill: A systematic review - Wulan Anugrah P.S; Dian Ramawati (Science Midwifery, 2026)
Problems in social and emotional development in children have been increasing in recent years Children with social emotional problems will become more introvert, experienced sleep disturbances, solitary violent behavior, lack of creativity, and the threat of cyberbullying, from this phenomenon, the right intervention is needed, one of which is play. intervention that has proven effective in developing social-emotional aspects is play. Play is not just a recreational activity, but has high therapeutic and educational value. Through play, children learn to manage emotions, resolve conflicts, empathize, and build cooperation skills.The purpose of this systematic review is to analyse the types of games and the success of games in improving social emotional development. This study uses a systematic review based on the Preferred Reporting Items for Systematic Review And Meta-Analysis (PRISMA) stage, articles were collected from PubMed, Google Scholar, ProQuest, Science Direct databases, from 2017 to 2024, Articles were selected according to the inclusion and exclusion criteria and critical appraisal was carried out using the JBI Instrument on the selected articles.The results of the review of articles from 2017-2024 obtained eight articles, five articles discuss modern games in improving early childhood social emotional development, three articles discuss traditional games in improving social emotional development, all articles agree that both modern and traditional games can improve social and emotional development with their respective advantages. It can be conclude that both traditional and modern games can enhance the social emotional development in early childhood.